Benefits and challenges of AIOPS adoption and usage in HEIs in developing countries - Funda, V.; Francke, E. (South African Journal of Higher Education, 2024)
Adopting Artificial Intelligence for IT Operations (AIOPS) holds transformative potential within Higher Education Institutions (HEIs) in developing countries. This systematic literature review delves into the benefits, challenges, and emerging trends associated with AIOPS integration in this context. The review encompasses studies published between 2013 and 2023, focusing on the academic, administrative, and operational dimensions of AIOPS adoption. The synthesis of 12 selected studies reveals a landscape where AIOPS augments pedagogical strategies, automates administrative tasks, and enhances institutional decision-making. Academic benefits manifest through personalised learning experiences, innovative pedagogical approaches, and predictive analytics for student success. However, the integration of AIOPS is full of challenges. Technical hurdles encompass data quality and availability, compatibility, and resource constraints, requiring comprehensive technological foundations. Organisational and cultural challenges necessitate strategies to mitigate change resistance, provide staff training, and address ethical considerations. The review identifies emerging patterns such as collaborative learning environments, data-driven institutional management, and the moral integration of AI in education. The interplay of benefits and challenges underscores the importance of a holistic approach involving educators, technologists, administrators, and policymakers. The findings illuminate the potential for HEIs to harness AIOPS's capabilities while navigating intricacies to foster an AI-enhanced educational landscape. The implications for HEIs encompass strategic investment in infrastructure, comprehensive staff training, and ethical frameworks for AI use. The paper concludes by advocating for an adaptive approach to AIOPS adoption, informed by the synthesis of benefits, challenges, and emerging trends, to shape the future of education in developing countries.